2020
DOI: 10.3390/jcm9092920
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on MicroRNA Profile in Tear Fluid to Predict Response to Anti-VEGF Treatments for Diabetic Macular Edema

Abstract: (1) Background: Intravitreal anti-vascular endothelial growth factor (anti-VEGF) is an established treatment for center-involving diabetic macular edema (ci-DME). However, the clinical response is heterogeneous. This study investigated miRNAs as a biomarker to predict treatment response to anti-VEGF in DME. (2) Methods: Tear fluid, aqueous, and blood were collected from patients with treatment-naïve DME for miRNA expression profiling with quantitative polymerase chain reaction. Differentially expressed miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 75 publications
0
12
1
Order By: Relevance
“…The other top-ranked miRNAs identified by bioinformatic analysis were miR-4500 and miR-4458. However, we did not find any literature on the role of miR-4500 and miR-4458 in endothelial dysfunction, whereas recent reports [52][53][54] have suggested a role for miR-98-5p in endothelial cells. Moreover, the complementary nucleotides between the target region of TMPRSS2 3′ untranslated region (3′-UTR) and miR-98-5p are evolutionarily highly conserved across different species, including humans, non-human primates, and rodents (Figure 1).…”
contrasting
confidence: 99%
“…The other top-ranked miRNAs identified by bioinformatic analysis were miR-4500 and miR-4458. However, we did not find any literature on the role of miR-4500 and miR-4458 in endothelial dysfunction, whereas recent reports [52][53][54] have suggested a role for miR-98-5p in endothelial cells. Moreover, the complementary nucleotides between the target region of TMPRSS2 3′ untranslated region (3′-UTR) and miR-98-5p are evolutionarily highly conserved across different species, including humans, non-human primates, and rodents (Figure 1).…”
contrasting
confidence: 99%
“…Through bioinformatics analysis, Matarese et al also identified miR-4500 and miR-4458 [218]. However, no evidence exists in the literature about their endothelial dysfunction roles, while other reports [220][221][222] precisely suggest a role for miR-98-5p in endothelial cells. TMPRSS2 is a highly polymorphic gene, and specific genetic variants of TMPRSS2 have been classified, indicating that their frequencies change with geographic location and origin [223][224][225].…”
Section: Alternative Approachmentioning
confidence: 99%
“…1 The main cause of DME is the onset of macular thickening. 17 VEGF overexpression plays a pivotal role in DME progression, but its mechanism and diagnostic role have remained elusive. Serum exosomal miRNAs have been identified as biomarkers of several diseases, although their value in DME has been unclear.…”
Section: Discussionmentioning
confidence: 99%